Discussing the motives to learn Russian as a foreign language during COVID-19 pandemic: psychopedagogical aspect - Nazartseva, Ekaterina (2021)
The article shows that the coronavirus pandemic has led to a rapid modernization of Russian education due to the widespread introduction of online learning. The features of the modern educational environment are considered, its advantages and disadvantages are analyzed. It is proved that psychologists and teachers should pay special attention to the study of the motives of learning Russian as a foreign language at the pre-university stage of training. Maintaining motivation will contribute to the success of training, maintaining the prestige of Russian education and, as a result, attracting foreign applicants and students to study in Russian universities.